Greenhouse disease of oil palm seedlings and their causal pathogen in UiTM Melaka Campus Jasin / Akmal Hakim Abdullah Hadi and Hamzah Abdul Aziz - Abdullah Hadi, Akmal Hakim; Abdul Aziz, Hamzah (Faculty of Plantation and Agrotechnology, 2018)
Malaysia is among the top countries in the world in producing oil palm. Nowadays, the number of oil palm production plays a significant role in Malaysia economic growth. The diseases that attack the oil palm leaves were became a major problem in the early growth stage of oil palm such as Culvularia leaf spot that caused by Culvularia sp., Fusarium wilt caused by Fusarium oxysporum f. sp elaeidis (Foe), Corticium leaf spot caused by Corticium solani. It was became a problem when hard to be eradicated and taken several methods to eliminate it. Therefore, the main objectives of this study were to recognize and define what type of leaf diseases and its causal agents on oil palm seedlings. Next, to determine disease incidence and distribution of leaf diseases on oil palm seedlings reared in the greenhouse structure. Last but not least, the purpose control on the disease that attacked oil palm seedlings. In this study, disease that I found in the greenhouse three UITM Jasin were found and isolated it to identify what type of disease that attack the oil palm seedlings leaves. In vitro studies, the sample of leaf diseases were collected and its causal agent induced to grow on PDA. Four type of diseases were identified which were Culvularia leaf spot, Fusarium wilt, Common spear rot and Rhizoctonia solani. The most leaf disease attacked on oil palm seedlings was Culvularia leaf spot at 41% incidences. The causal agent for each of leaf diseases have been identified after isolation and observation under microscope based on their microscopic characteristics (Conidia and hyphae). The most recommend control methods have been identified to control common spear rot, Rhizoctonia solani and Culvularia leaf spot was using the biological control method such as Bacillus subtillis, Tricoderma harzianum and wild basidiomycetes. But the most effective approach in controlling fusarium wilt was using the resistances cultivars.